Kompetensi Dosen AMI AIPI Makassar Dalam Menghasilkan Pelaut Sesuai Standar Nasional Dan Internasional (LPPM UKI Toraja, 2019)
The Competence of AMI AIPI Makassar lecturer in producing seafarers according to National dan International Standards ( guided by Prof. Dr. Ir.H. M.Hattah Fattah, MS and Dr. Ir. H. Abdul Rauf, MS ). Thisresearch aims to determine (1) the competence of lecturers and (2) analyze the influence of lecturers competence on the competence of alumni AMI AIPI Makassar in order to produce seafarers in accordance with the national and international standards. The method used is quantitative method with qualitative data support. Data was collected by direct observations techniques, in-depth interviews, questionnaires and documentation. Respondents were collected based on random sampling. Data were analyzed descriptively by using frequenct table calculation to score with scale range, and simple linier regression analysis to see the influence of lecturer competence to alumni competence. The data are presented in the form of korelais tables and are described based on the results of the calculations, followed by drawing conclucions and suggestions. The results showed that (1) The Competence of AMI AIPI Makassar lecturers was termed in either category based on the scale range. The results on the competence of lecturers is obtained through the distribution of questionnaires to the alumni which produce a good scale range of scales. The standard of the competence of alumni is obtained through the range of scale from the company of service user of AMI AIPI Makassar Alumni with good category, fulfilling the standard of the shipping company. The result of simple linear regression analysis stated (2) The influence of pedagogic competence on alumni competence is strong enough. Similarly, the competence of personality and professional. While the social competence of prayer has a strong influence on the competence of alumni.